“Guds Israel” i Gal 6,16 og “hele Israel” i Rom 11,26 - Müller, Mogens (Dansk Teologisk Tidsskrift, 2015)
Earlier interpreters claimed two possibilities with respect to the expression “God’s Israel” in Galatians 6,16: Either it was the Christians irrespective of their ethnical descendence, or it was the Jewish Christians. In the later years a third possibility has made its appearance, namely that it is the real Israel which Paul then has not forgotten and the destiny of which he returns to in Romans 9-11. This article argues that only the first solution corresponds to Paul’s thinking where nobody reach salvation without a faith in Christ working through love. Thus there is only one candidate to the title “God’s Israel” and that is the church.